Tradisi Menulis Ulama Indonesia (Abad ke-19 s.d 21) - Indah Cendikia NST; Nurul Humaidi (Global Education Journal, 2026)
The phenomenon of the writing tradition of Indonesian scholars today shows that there is an integral part in the development of Islamic intellectuals that have strong theological roots and a strategic role in building Islamic civilization. This article aims to analyze the doctrinal roots of the writing tradition in Islam, the dynamics of the ups and downs, especially in Indonesia, the map of scholars' scientific treasures, and the profile of prolific writers and their influences. This research uses a qualitative approach with the type of library research. The results of the study show that the writing tradition of Indonesian scholars from the 19th to the 21st century developed dynamically, influenced by internal factors such as religious and external motivations such as socio-political conditions as well as the development of the times and technology. Theoretically, this tradition can be understood through the perspective of social constructivism and scientific habitus that shape the literacy culture of scholars.